Multi-component composite electrolyte, preparation method and application of multi-component composite electrolyte in zinc ion battery
By introducing acetamide and asparagine into the ZnSO4 electrolyte of an aqueous zinc ion battery, a multi-component composite electrolyte is formed, which solves the problems of hydrogen evolution reaction, corrosion and kinetics of the battery at extreme temperatures, and achieves high-performance wide temperature domain adaptability and fast and reversible Zn deposition kinetics.
Patent Information
- Application Number
- CN202411669759.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-11-21
AI Technical Summary
Water-based zinc ion batteries have thermodynamic hydrogen evolution reaction, corrosion and passivation problems under extreme temperature conditions. Kinetic growth and the formation of dead zinc affect their rapid redox kinetics and charge and discharge reversibility.
By introducing acetamide and asparagine into the ZnSO4 electrolyte, a multi-component composite electrolyte is formed, and the solvation structure and hydrogen bond network are optimized, which compensates for the negative kinetic effects brought by organic solvents, and improves the wide temperature domain adaptability and Zn deposition kinetics of the battery.
The stable cycling performance of aqueous zinc ion batteries in a wide temperature range is achieved, the stability and corrosion resistance of electrode/electrolyte interface are enhanced, and the reversibility and electrochemical performance of charge and discharge are improved.
Smart Images

Figure HDA0005145524110000011 
Figure HDA0005145524110000012 
Figure HDA0005145524110000021
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of zinc ion batteries and relates to a multi-component composite electrolyte, a preparation method and application thereof in zinc ion batteries. Background Art
[0002] At present, efficient and renewable clean energy has become a research hotspot in the global energy field. Among the potential batteries for the next generation of large-scale energy storage, aqueous zinc-ion batteries are considered to be one of the most promising research due to their high energy density, safety, and environmental friendliness. As the anode of aqueous zinc-ion batteries, Zn metal has an ultra-high volumetric capacity (5855 mAh cm -3 ), lower cost (about 25% cheaper than Li) and moderate redox potential (-0.76V vs. standard hydrogen electrode). However, the practical application of aqueous zinc-ion batteries remains challenging, mainly due to the following reasons: thermodynamic hydrogen evolution reaction, corrosion and passivation, as well as kinetic dendrite growth and dead zinc formation, which will continue to intensify under extreme temperature conditions. At the same time, today's global climate is variable and diverse, and many application scenarios require aqueous zinc-ion batteries to operate over a wide temperature range. Therefore, it is very challenging to ensure their fast redox kinetics and high charge and discharge reversibility in this case.
[0003] In order to alleviate such problems, many scholars have proposed effective ideas. Introducing organic co-solvents into aqueous electrolytes can effectively improve the wide temperature range adaptability of batteries. However, the introduction of organic solvents will increase the viscosity of the electrolyte and reduce the ionic conductivity, thereby affecting the polarization and rate performance of the battery, and will also cause safety and environmental protection issues. We realize that it is difficult to achieve both good wide temperature range performance and fast, reversible Zn deposition kinetics by regulating the composition of the electrolyte using only a single substance. Therefore, we speculate that additives that can compensate for the sacrificial Zn deposition kinetics can be introduced into the system to avoid excessively amplified polarization, and ultimately enable the battery to exhibit improved cycle performance and ionic conductivity. To this end, the present invention is proposed. Summary of the invention
[0004] In view of the shortcomings of the prior art, especially the thermodynamic hydrogen evolution, corrosion and passivation of aqueous zinc ion batteries, as well as the kinetic problems of dendrite growth and dead zinc, the present invention provides a multi-component composite electrolyte and a preparation method and its application in zinc ion batteries. The present invention compensates for the negative kinetic effects of organic solvents to provide ZnSO 4 The introduction of acetamide into the electrolyte improves the battery's adaptability to a wide temperature range, and the introduction of asparagine compensates for the reversibility of Zn deposition kinetics, thereby achieving an aqueous zinc-ion battery with long normal / low temperature cycle life, stable electrode / electrolyte interface, and strong corrosion resistance.
[0005] To achieve the above object, the technical solution of the present invention is as follows:
[0006] A method for preparing a multi-component composite electrolyte comprises the following steps:
[0007] Acetamide and asparagine were added to ZnSO 4 The solution is stirred and mixed evenly, and allowed to stand to obtain a multi-component composite electrolyte.
[0008] According to the preferred embodiment of the present invention, the ZnSO 4 The concentration of the solution is 1-2 mol / L.
[0009] According to the preferred embodiment of the present invention, the acetamide and ZnSO 4 ZnSO in solution 4 The molar ratio is 6-9:2.
[0010] According to the preferred embodiment of the present invention, the asparagine and ZnSO 4 ZnSO in solution 4 The molar ratio is 0.15-0.20:2.
[0011] In summary, the present invention combines acetamide, asparagine and ZnSO 4 The ratio of is controlled within the scope of the present invention, which can ensure that acetamide and asparagine can maximize their own characteristics and synergistic effects to obtain a high-performance aqueous zinc ion battery.
[0012] Preferably according to the present invention, the stirring temperature is 40-50° C., the stirring time is 20-40 min; and the stirring is performed under water bath heating conditions.
[0013] Preferably according to the present invention, the standing temperature is room temperature, and the standing time is 1-3 hours; the room temperature refers to 25±5°C.
[0014] The present invention also provides a multi-component composite electrolyte, which is prepared by the above-mentioned preparation method.
[0015] According to the present invention, the above-mentioned multi-component composite electrolyte is used in an aqueous zinc ion battery.
[0016] The present invention also provides an aqueous zinc ion battery, comprising a negative electrode, a positive electrode, a separator and the multi-component composite electrolyte.
[0017] Preferably according to the present invention, the negative electrode is metallic zinc.
[0018] According to the preferred embodiment of the present invention, the positive electrode includes a current collector, an active ingredient, a conductive agent and a binder, which are all commonly used components in the art; further preferably, the positive electrode is NH4 V 4 O 10 The positive electrode was prepared as follows: NH 4 V 4 O 10 Grind into powder, mix with conductive carbon black and polyvinylidene fluoride in a mass ratio of 7:2:1, add solvent and grind into a uniform slurry, and evenly apply it on the carbon cloth to obtain NH 4 V 4 O 10 positive electrode; the solvent is N-methylpyrrolidone, the NH 4 V 4 O 10 The total mass ratio of the conductive agent conductive carbon black and the binder polyvinylidene fluoride to the volume of the solvent is 1g:12mL; NH 4 V 4 O 10 The loading capacity is 1.8-2.2 mg / cm 2 .
[0019] Preferably according to the present invention, the diaphragm is a glass fiber membrane.
[0020] Preferably according to the present invention, the aqueous zinc ion battery is a 2032 button battery.
[0021] Under the action of acetamide, the multi-component composite electrolyte prepared by the present invention has different 4 The optimized solvation structure and hydrogen bond network of the electrolyte can effectively alleviate the hydrogen evolution reaction, corrosion and passivation caused by active water in thermodynamics, while enhancing the low temperature tolerance of the electrolyte, enabling it to have the ability to cycle charge and discharge for a long time at low temperatures. Asparagine additive molecules can enter the inner layer of the double electrical layer, that is, the inner Helmholtz plane, and thus easily interact with the surface of the Zn negative electrode to form an organic-inorganic composite solid-electrolyte interphase (SEI). This SEI can improve and reduce the Zn 2+ Desolvation activation energy, accelerating charge transfer during charge and discharge, and regulating Zn at the electrode / electrolyte interface 2+ concentration gradient, ultimately achieving fast, dendrite-free Zn deposition kinetics.
[0022] On the other hand, the present invention has found through research that the introduction of organic co-solvent acetamide can usually reduce the freezing point of the electrolyte, thereby improving the antifreeze performance, but it will inevitably reduce the conductivity and ion migration kinetics of the electrolyte. However, the additional introduction of asparagine as an electrolyte additive into the system can offset this adverse effect, and the two show excellent synergistic effects, thereby having excellent electrochemical performance.
[0023] The present invention can prepare a multi-component composite electrolyte, and can solve the problems of reduced conductivity, enhanced polarization and poor rate performance caused by the introduction of an organic solvent with enhanced temperature adaptability. The organic co-solvent selected in the present invention is a common colorless organic solvent-acetamide, which is commonly used as an intermediate and solvent in organic synthesis, and its characteristics include a high boiling point, good polarity and low price. Considering the factor of whether multiple components can coexist, another component selected is asparagine, one of the common twenty amino acids. As amide substances, the two can stably coexist in ZnSO 4 The multi-component composite electrolyte can reconstruct the hydrogen bond network and regulate the Zn 2+ The solvation structure forms SEI and works together to enhance the electrochemical performance of aqueous zinc-ion batteries.
[0024] The electrolyte prepared by the present invention has a unique solvation structure and a reconfigured hydrogen bond network as well as enhanced adaptability to a wide temperature range. In addition, it has excellent charge transfer rate and Zn deposition kinetics. These characteristics exhibit excellent electrochemical performance through their excellent synergistic effect.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] 1. The present invention uses organic co-solvent acetamide in ZnSO 4 The solution is evenly mixed to form a unique Zn 2+ The electrolyte has a solvation structure and a reconstructed hydrogen bond network; while asparagine can undergo interfacial chemistry with the Zn anode to form a unique organic-inorganic SEI, accelerating the Zn deposition kinetics.
[0027] 2. The electrolyte of the present invention has multiple components that work together to exert the above characteristics, and these characteristics, through synergistic effects, show significantly enhanced and excellent electrochemical performance.
[0028] 3. The preparation process of the electrolyte of the present invention adopts a stirring method under water bath heating conditions. This method avoids the dilemma that acetamide absorbs a lot of heat during the dissolution process, resulting in a drop in temperature and difficulty in fully mixing the solution, and also accelerates the dissolution process of asparagine.
[0029] 4. The electrolyte additive selected by the present invention is green, environmentally friendly, and inexpensive. It can reduce costs without compromising its safety, and is very suitable for the system of aqueous zinc ion batteries.
[0030] 5. The present invention relates to a multi-component composite electrolyte, which, through the synergistic effect of its multiple components, inhibits a series of side reactions on the zinc metal negative electrode, enhances the adaptability of the electrolyte in a wide temperature range, and plays a certain reference role in broadening the energy material system. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0032] Figure 1 Fourier transform infrared spectra (FTIR) of the electrolytes prepared in Example 1 and Comparative Examples 1-3.
[0033] Figure 2 H in the electrolyte prepared in Example 1 and Comparative Examples 1-3 2 O's 1 H nuclear magnetic resonance spectrum (NMR).
[0034] Figure 3 It is the Raman spectrum fitting diagram (Raman) of the OH stretching vibration peak in the electrolyte prepared in Example 1 and Comparative Examples 1-3.
[0035] Figure 4 This is a graph showing the relationship between the acetamide addition concentration in Experimental Example 1 and the freezing point of the electrolyte and the battery conductivity.
[0036] Figure 5 This is a diagram of the cycling performance of batteries prepared with different asparagine addition concentrations in Experimental Example 2.
[0037] Figure 6 This is the linear voltammetry (LSV) curve of the three-electrode measurement system prepared in Experimental Example 3.
[0038] Figure 7 Linear polarization curve (LP) of the three-electrode measurement system prepared in Experimental Example 3.
[0039] Figure 8 X-ray photoelectron spectroscopy (XPS) of the Zn electrode after sputtering at different depths on the surface of the Zn / / Zn symmetric battery prepared in Experimental Example 4 after cycling.
[0040] Fig. 9 The desolvation activation energy obtained by fitting the impedance of the Zn / / Zn symmetric battery prepared in Experimental Example 4 at different temperatures.
[0041] Fig.10 This is the cycling performance diagram of the Zn / / Zn symmetrical battery prepared in Experimental Example 4 at -25°C.
[0042] Fig.11 This is a scanning electron microscope (SEM) image of the Zn electrode surface of the Zn / / Zn symmetric battery prepared in Experimental Example 4 after cycling.
[0043] Fig.12 Zn / / NH prepared in Experimental Example 5 4 V4 O 10 Cycling performance of the full cell at a current density of 4 A / g. DETAILED DESCRIPTION
[0044] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0045] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0046] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in combination with specific embodiments and comparative examples.
[0047] ZnSO used in the examples and comparative examples 4 7H 2 O, acetamide and asparagine (CAS No. 70-47-3) have molecular weights of 287.56 g mol -1 , 59.07 g mol -1 and 132.12 g mol -1 .
[0048] Example 1
[0049] A method for preparing a multi-component composite electrolyte comprises the following steps:
[0050] Take 2 mol / L ZnSO 4 10 mL of the solution was added to a sample bottle, and then 5.31 g of acetamide and 0.264 g of asparagine were added. The resulting mixed solution was placed in a 50°C water bath and stirred for 30 min. The solution was taken out, cooled naturally to room temperature, and allowed to stand at room temperature for 2 h to obtain a multi-component composite electrolyte, which was recorded as ZS-Dual.
[0051] Example 2
[0052] A method for preparing a multi-component composite electrolyte is as described in Example 1, except that the amount of asparagine added is 0.198 g, and the resulting composite electrolyte is recorded as ZS-9Ace-0.15Asn.
[0053] Comparative Example 1
[0054] Using 2 mol / L ZnSO 4 The solution is used as the electrolyte and is denoted as ZS.
[0055] Comparative Example 2
[0056] A method for preparing a multi-component composite electrolyte is as described in Example 1, except that asparagine is not added, and the resulting composite electrolyte is recorded as ZS-Ace.
[0057] Comparative Example 3
[0058] A method for preparing a multi-component composite electrolyte is as described in Example 1, except that acetamide is not added, and the resulting composite electrolyte is recorded as ZS-Asn.
[0059] Comparative Example 4
[0060] A method for preparing a multi-component composite electrolyte is as described in Example 1, except that the amount of asparagine added is 0.132 g, and the resulting composite electrolyte is recorded as ZS-9Ace-0.10Asn.
[0061] Comparative Example 5
[0062] A method for preparing a multi-component composite electrolyte is as described in Example 1, except that the amount of asparagine added is 0.33 g, and the resulting composite electrolyte is recorded as ZS-9Ace-0.25Asn.
[0063] The comprehensive analysis is as follows:
[0064] Figure 1-3 The Fourier transform infrared spectra of the electrolytes prepared in Example 1 and Comparative Examples 1-3, and the H 2 O's hydrogen nuclear magnetic resonance spectrum and Raman spectrum. OH, C=O and SO in Fourier infrared spectrum 4 2- The blue shift of stretching vibration proves that the acetamide-dominated Zn 2+ Changes in the solvation structure. Figure 2 It can be seen that after the addition of acetamide (asparagine), it forms a hydrogen bond with the hydroxyl group in water, and H contributes a lone pair of electrons, so 1 H(H 2 O) has a reduced electron density, which is manifested as 1 The chemical shift of H increases and the peak moves downfield. Figure 3 For Raman spectroscopy, we will use 3000-3700cm -1 The stretching vibration band of OH between them is reversed into two Gaussian peaks (Iw mainly contributed by hydrogen bonds and Iw mainly contributed by non-hydrogen bonds). S), the results show that under the action of acetamide, the ratio of hydrogen bonds between water molecules is greatly reduced and the disorder of hydrogen bonds is increased, resulting in a lower liquid-solid temperature limit.
[0065] Test Example 1
[0066] The relationship between acetamide addition concentration, electrolyte freezing point and battery conductivity was studied as follows:
[0067] Take 4 portions of 2 mol / L ZnSO 4 10 mL of electrolyte was added to a sample bottle, and then 1.77 g, 3.54 g, 5.31 g and 7.08 g of acetamide were added respectively. The resulting solution was stirred continuously for 30 min at room temperature and allowed to stand at room temperature for 2 h to obtain electrolytes, which were respectively recorded as ZS-3Ace, ZS-6Ace, ZS-9Ace and ZS-12Ace.
[0068] Aqueous zinc ion Zn / / Zn symmetric batteries (2032 button cells) were assembled using metallic zinc with a diameter of 12 mm as both the negative electrode and the counter electrode, a glass fiber membrane (GF / Dwhatman) as a separator, and various electrolytes prepared as described above as electrolytes.
[0069] The relationship between different acetamide addition concentrations and the freezing point of the electrolyte and the battery conductivity is as follows: Figure 4 As shown by Figure 4 It can be seen that with the increase of acetamide concentration, the conductivity and freezing point have different degrees of decrease. Considering comprehensively, acetamide and ZnSO 4 The molar ratio of acetamide to ZnSO is selected to be 6-9:2. 4 The optimal molar ratio is 9:2.
[0070] Test Example 2
[0071] The relationship between asparagine addition concentration and battery cycle performance was studied
[0072] Metal zinc with a diameter of 12 mm was used as both the negative electrode and the counter electrode, a glass fiber membrane (GF / DWhatman) was used as a separator, and the electrolytes prepared in Example 1, Example 2, and Comparative Examples 4-5 were used as electrolytes to assemble aqueous zinc ion Zn / / Zn symmetric batteries (2032 button batteries), and their cycle performance was tested.
[0073] Figure 5 The figure is a cycle performance diagram of an aqueous zinc ion Zn / / Zn symmetric battery assembled using the electrolytes prepared in Example 1, Example 2, and Comparative Examples 4-5 as electrolytes. The results show that the addition of asparagine Asn can significantly improve the cycle stability and reduce polarization, but too much asparagine will reduce the cycle performance of the battery, and acetamide, asparagine and ZnSO4 The optimal molar ratio is 9:0.2:2.
[0074] Test Example 3
[0075] A three-electrode electrolytic cell was prepared using the electrolyte prepared in Example 1 and Comparative Examples 1-3 as the electrolyte.
[0076] A 100 μm thick metal zinc was used as the working electrode, a stone mill rod was used as the counter electrode, an Ag / AgCl electrode protected in a saturated KCl aqueous solution was used as the reference electrode, and 40 mL of electrolyte was added to a 50 mL electrolytic cell to form a three-electrode measurement system.
[0077] Figure 6 and Figure 7 The three-electrode system linear sweep voltammetry curve and linear polarization curve are respectively used. Since acetamide can replace the original active water molecules of the solvation sheath, the hydrogen evolution reaction is inhibited during the desolvation process. Therefore, under the action of acetamide, the hydrogen evolution potential of ZS-Ace of Comparative Example 2 and ZS-Dual of Example 1 shifts to the negative direction, proving the anti-hydrogen evolution ability of the Zn electrode. It is worth noting that the addition of asparagine will aggravate the hydrogen evolution reaction to a certain extent, which may be the reason why the hydrolysis reaction of asparagine carboxylate reduces the pH. Figure 7 In the experiment, under the action of acetamide, the corrosion current density of ZS-Ace and ZS-Dual was greatly reduced, indicating the enhanced corrosion resistance of Zn electrode. The above results prove that the electrolyte prepared in Example 1 has significantly improved resistance to hydrogen evolution and corrosion.
[0078] Test Example 4
[0079] Zn / / Zn symmetrical button cells were prepared using the electrolytes prepared in Example 1 and Comparative Examples 1-3 as electrolytes.
[0080] Metal zinc with a diameter of 12 mm was used as both the negative electrode and the counter electrode, a glass fiber membrane (GF / DWhatman) was used as a separator, and the electrolyte prepared in Example 1 and Comparative Examples 1-3 was used as the electrolyte to assemble an aqueous zinc ion Zn / / Zn symmetric battery (2032 button cell).
[0081] Figure 8 XPS spectra of C1s, N1s, O1s and S2p at different depths of the Zn electrode after cycling of an aqueous zinc ion Zn / / Zn symmetric battery prepared with the electrolyte ZS prepared in Comparative Example 1 and the electrolyte ZS-Dual prepared in Example 1, proving the formation of an organic-inorganic hybrid SEI induced by asparagine. Fig. 9The calculated values of the desolvation activation energy of the electrolytes (ZS, ZS-Ace, ZS-Asn and ZS-Dual) prepared in Example 1 and Comparative Examples 1-3 show that the desolvation kinetics are significantly enhanced under the action of asparagine.
[0082] The cycle performance curve of the aqueous zinc ion Zn / / Zn symmetric battery prepared using the electrolyte prepared in Example 1 at -25°C is as follows: Fig.10 As shown in the figure, it can be seen that the battery using ZS-Dual can maintain a long and stable cycle under different conditions. The Zn surface morphology of the battery prepared with different electrolytes after 50 cycles at room temperature was observed using a scanning electron microscope. Fig.11 As shown, ZS-Dual exhibits a very dense and flat morphology, which proves the reliability of the present invention.
[0083] Test Example 5
[0084] The multi-component composite electrolyte ZS-Dual prepared in Example 1 and the electrolyte (ZS) prepared in Comparative Example 1 were prepared into Zn / / NH 4 V 4 O 10 Full battery button cell.
[0085] The active substance NH 4 V 4 O 10 , conductive carbon black and binder polyvinylidene fluoride were mixed in a mass ratio of 7:2:1, then dissolved in NMP and ground into a uniform slurry. 4 V 4 O 10 The total mass ratio of the conductive agent conductive carbon black and the binder polyvinylidene fluoride to the volume of NMP is 1g:12mL; the slurry is evenly coated on a carbon cloth with a diameter of 12mm, and the loading amount is 2mg / cm 2 Then, the above-mentioned 12 mm electrode piece was used as the positive electrode, a 12 mm diameter metal zinc was used as the negative electrode, a glass fiber membrane (GF / D Whatman) was used as the separator, and the multi-component composite electrolyte prepared in Example 1 was used as the electrolyte to assemble an aqueous zinc ion Zn / / NH 4 V 4 O 10 Battery (2032 button cell).
[0086] Fig.12 It is Zn / / NH 4 V 4 O 10 Cyclic performance curve of the full battery. The results show that the Zn / / NH4 V 4 O 10 The full battery still has a capacity retention rate of 80% after 1200 cycles at a current density of 4A / g, which is much higher than that of Zn / / NH 4 V 4 O 10 It has a capacity retention rate of 45% after 500 cycles and an ultra-high coulombic efficiency of 99.99%.
[0087] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a multi-component composite electrolyte, characterized in that: The steps include: Add acetamide and asparagine to the ZnSO4 solution, stir and mix evenly, and let stand to obtain a multi-component composite electrolyte.
2. The method for preparing the multi-component composite electrolyte according to claim 1, characterized in that: The concentration of the ZnSO4 solution is 1-2 mol / L.
3. The method for preparing the multi-component composite electrolyte according to claim 1, characterized in that: The molar ratio of the acetamide to the ZnSO4 in the ZnSO4 solution is 6-9:
2.
4. The method for preparing the multi-component composite electrolyte according to claim 1, characterized in that: The molar ratio of asparagine to ZnSO4 in the ZnSO4 solution is 0.15-0.20:
2.
5. The method for preparing the multi-component composite electrolyte according to claim 1, characterized in that: The stirring temperature is 40-50° C., the stirring time is 20-40 min, and the stirring is performed under water bath heating conditions.
6. The method for preparing the multi-component composite electrolyte according to claim 1, characterized in that: The standing temperature is room temperature, and the standing time is 1-3 hours.
7. A multi-component composite electrolyte, characterized in that: The preparation method according to claim 1 is used for preparation.
8. Use of the multi-component composite electrolyte according to claim 7 in aqueous zinc ion batteries.
9. An aqueous zinc ion battery, characterized in that: It comprises a negative electrode, a positive electrode, a separator and the multi-component composite electrolyte as claimed in claim 7.
10. The aqueous zinc ion battery according to claim 9, characterized in that: The negative electrode is metal zinc; The positive electrode comprises a current collector, an active component, a conductive agent and a binder, all of which are commonly used components in the art; preferably, the positive electrode is NH4V4O 10 The positive electrode was prepared as follows: NH4V4O 10 Grind into powder, mix with conductive carbon black and polyvinylidene fluoride in a mass ratio of 7:2:1, add solvent and grind into a uniform slurry, and evenly apply it on the carbon cloth to obtain NH4V4O 10 positive electrode; the solvent is N-methylpyrrolidone, the NH4V4O 10 , the total mass ratio of the conductive agent conductive carbon black and the binder polyvinylidene fluoride to the volume of the solvent is 1g:12mL; NH4V4O 10 The loading capacity is 1.8-2.2 mg / cm 2 ; The diaphragm is a glass fiber membrane; the aqueous zinc ion battery is a 2032 button battery.
Citation Information
Patent Citations
Zinc battery electrolyte additive
CN108649266A
Aqueous zinc ion battery electrolyte based on eutectic salt electrolyte
CN113206283A
Electronic device including antenna structure
KR1020230037352A